The Influence of Exploration Costs and Leverage on Eaarnings Management with Firm Size as a Moderating Variable - Rachman, Khairul Arief; Nugroho, Lucky (Business, Management & Accounting Journal (BISMA), 2025)
Increasing demands for transparency from stakeholders encourage financial sector companies to strengthen Sustainability Reporting Disclosure (SRD). However, variations in the level of disclosure despite uniform regulations create research gaps related to the factors that influence them. This study aims to examine the influence of board size, gender diversity, Green Financing, and Return on Assets (ROA) on SRD, as well as the role of company size as a moderator. Using a quantitative approach, this study analyzes secondary data from financial sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. Moderation regression is used to test the direct influence and interaction of variables. The results showed that board size, gender diversity, and Green Financing had a significant positive effect on SRD, while ROA had a positive but insignificant effect. Additionally, company size moderates the influence of board size, gender diversity, and Green Financing; however, it does not moderate the relationship between ROA and SRD. These findings reinforce the stakeholder theory that environmental governance and performance factors, when scaled up by the company, enhance the quality of sustainability disclosure. The novelty of the study lies in the simultaneous integration of governance, Green Financing, profitability, and the moderation of company size in industries with strict regulations.